IMPLEMENTATION OF THE TRANSIT ORIENTED DEVELOPMENT (TOD) CONCEPT AT TANAH ABANG STATION, TANAH ABANG, CENTRAL JAKARTA - Taki, Herika Muhamad; Alisha Putri Negara; Parapat, Ros Dwita Gresia (Jurnal Lingkungan dan Kota, 2025)
Reduced land for development, congestion due to the large number of private transportation, and air pollution are some of the problems of big cities like Jakarta that deserve to be solved with efficient solutions. Transit Oriented Development (TOD) is a concept for developing a transit facility that has the principle of maximizing land and improving adequate public facilities. Tanah Abang Station is one of the largest stations in Jakarta which acts as a Primary Activity Center. In this regard, planning is needed so that the Tanah Abang station is integrated with other modes of transportation to increase the effectiveness of the station in the development of the area and activities around it. The research aims to see the suitability of the application of the TOD area at Tanah Abang Station by analyzing the supporting facilities there and the availability of transportation facilities with the help of ArcGis software to determine the suitability conditions of the TOD concept